Describing the Accumulation, Concentration, and Amplification Effects of MPs Through the Food Chain - Dagdelen, Ulku; Turkyilmaz, Dogan; Esenbuga, Nurinisa (Current Nutrition & Food Science, 2025)
Microplastics (MP) are new pollutants that threaten the ecological environment and, therefore, human and animal health. Given the extensive utilization of plastics across various domains, MPs are commonly detected in the atmosphere, water bodies, terrestrial regions, and living organisms. Important accumulation points of MPs are air, soil, and water ecosystems. This study aims to summarize how animals are exposed to environmental MPs, identify the specific organs where these MPs accumulate, and assess the risks associated with different foods. The urrent research on MP pollution in ecosystems generally focuses on organisms living in water and soil, but unfortunately, there are significant deficiencies in the transmission routes of MPs in the food chain from soil to table. MPs build up in animals across the food chain, and their presence in animal-derived food products intensifies during processing and packaging. The transfer of MPs to food-producing animals has been understudied, particularly with regard to the important role of livestock in converting plant nutrients into proteins required for human consumption. It is understood that more research is needed, especially for contamination in animal foods. Conducting comprehensive risk assessments of MPs throughout the entire food chain is extremely important for food safety.
Keywords: COVID-19